Avoiding the emergence of contrast-induced acute kidney injury in acute coronary syndrome: routine hydration treatment. Issue 5 (13th October 2020) - Arslan, Sukru; Yildiz, Ahmet; Dalgic, Yalcin; Batit, Servet; Kilicarslan, Onur; Ser, Ozgur Selim; Dalgic, Sadiye Nur; Kocas, Cuneyt; Abaci, Okay
Abstract : Background: Patients with acute coronary syndrome (ACS) have about a three-fold risk for developing contrast-induced acute kidney injury(CI-AKI). Investigating studies on routine hydration therapy have frequently included patients with stable coronary artery disease and high risk of CI-AKI [estimated glomerular filtration rate (eGFR) < 60 ml/min]. However, data on routine hydration treatment in non-ST segment elevation myocardial infarction (NSTEMI) patients with eGFR ≥60 ml/min are insufficient. We aimed to investigate the association between routine hydration therapy and CI-AKI development in NSTEMI patients at low risk for nephropathy. Methods and results: We randomly assigned a total of 401 NSTEMI patients to two groups: the routine hydration group (198 patients) and the nonhydration group (control group) (203 patients). Intravenous hydration with isotonic saline (1 ml/kg/h, 0.9% sodium chloride) was given for 3–12 h before and 24 h after contrast exposure to the hydration group. CI-AKI was defined as the increase in serum creatinine values 0.5 mg/dl or 25% between 48 and 72 h after the invasive procedures. In our study, the incidence of CI-AKI development in the routine hydration group (7.1%) was significantly lower than in the nonhydration group (14.1%) ( P : 0.02). This study revealed that older age, amount of contrast media, and routine hydration were independent risk factors for developing CI-AKI ( P  < 0.01, P : 0.04, P  < 0.01, respectively). Conclusion: We found that preprocedural and postprocedural intravenous hydration therapy reduces the development of CI-AKI in patients with NSTEMI at low risk for CI-AKI. We suggest administering routine hydration therapy in all ACS patients regardless of eGFR values.